2015
DOI: 10.1007/s10354-015-0356-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of pharmacological doses of ascorbate on cancer cells

Abstract: Intravenous application of high-dose ascorbate (vitamin C) has been used in complementary medicine since the 1970s to treat cancer patients. In recent years it became evident that high-dose ascorbate in the millimolar range bears selective cytotoxic effects on cancer cells in vitro and in vivo. This anticancer effect is dose dependent, catalyzed by serum components and mediated by reactive oxygen species and ascorbyl radicals, making ascorbate a pro-oxidative pro-drug that catalyzes hydrogen peroxide productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…Though ROS and H 2 O 2 are well known factors mediating PAA-induced cancer cell death (Espey et al, 2011, Levine et al, 2011), a single molecular mechanism cannot explain these observations because multiple pathways are involved in the downstream effects of ROS and H 2 O 2 (Venturelli et al, 2015). Necorosis, caspase-dependent and caspase-independent apoptosis, and autophagy were reported in ascorbate-induced cell death in different types of cancer (Chen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Though ROS and H 2 O 2 are well known factors mediating PAA-induced cancer cell death (Espey et al, 2011, Levine et al, 2011), a single molecular mechanism cannot explain these observations because multiple pathways are involved in the downstream effects of ROS and H 2 O 2 (Venturelli et al, 2015). Necorosis, caspase-dependent and caspase-independent apoptosis, and autophagy were reported in ascorbate-induced cell death in different types of cancer (Chen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Ascorbate has been shown to increase the effectiveness of various anticancer treatments. 18,19 Mixed micelles composed of TPGS and AP are nanosized colloidal particles with a hydrophobic core and a hydrophilic corona. The hydrophobic segment forms the core of the micelles that solubilize the hydrophobic drug molecules, and the hydrophilic segment forms the corona that provides compatibility of the micelles in the aqueous environment.…”
Section: Zhang Et Almentioning
confidence: 99%
“…Ascorbate has been well documented to reduce the incidence of most malignancies in humans, but most of the treatments require high-dose ascorbate6789. Recent pharmacological experiment reports have revealed that orally administered ascorbate, even at very large and frequent dose, marginally increases plasma concentrations from 0.07 mM to a maximum of 0.22 mM10.…”
mentioning
confidence: 99%